The Influence of Communication and Leadership to The Performance of Employee at Orthopaedic Hospital Prof.Dr.R. Soeharso of Surakarta - Ahmed, Aissa Hamed Ali, Dr. Amin Mustofa, M.HA, Drs. Anton Agus Setyawan, SE., M.Si (2014)
The purpose of this study is analysing influence communication on performance, leadership on performance and communication, and leadership on performance of employee at the Orthopaedic Hospital of Prof.Dr.R. Soeharso of Surakarta. This research is quantitative, by taking samples at Prof.DR.R. Soeharso of Orthopaedic at Jl. A. Yani, Pabelan, Kartasura, Surakarta, Central Java, Indonesia, 57162. The study population and sample as many as 664 employees were taken by 70 employees. The technique of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results obtained showed that Communications positive and significant effect on employee performance at Orthopaedic hospital Prof.Dr.R. Soeharso of Surakarta. Leadership positive and significant effect on employee performance at Orthopaedic hospital Prof.Dr.R. Soeharso of Surakarta. Communication and Leadership positive and significant effect on employee performance at Orthopaedic hospital Prof.Dr.R. Soeharso of Surakarta.